GENERAL CORRELATIONS FOR THE PERFORMANCE PREDICTION OF STRIP FIN PLATE-FIN SURFACES - Abu-khader, Mazen M.; Polley, Graham T. (Journal of Applied Engineering Science, 2025)
The paper presents a theoretical study approach to the Nusselt number and friction factor characteristics in strip fin surfaces. Extensive analyses were conducted on the thermal and hydraulic performances of off-set strip fin surfaces using the experimental data provided by Kays & London [1] and Shah and London [2,3]. General relationships were developed to predict the hydraulic and thermal performances giving accurate predictions across all flow regimes for a wide range of common strip geometries. The pressure drop encountered during flow through channels having off-set strip fins is affected by both flow disruption and flow blockage. Flow disruption appears to be the dominant factor in the laminar flow region. Under turbulent flow conditions, both effects were considered. Laminar flow heat transfer is well predicted if the Graetz Number is based on four-time strip fin length. Turbulent flow heat transfer is found to be proportional to the square root of the friction factor.